Konsep Hadith Mawdu‘i Menurut Perspektif Pengkaji Hadith Kontemporari: Antara Dirasah Al-Mawdu‘Iyyah min Al-Hadith dan Syarh Al-Mawdu‘I li Al-Hadith: The Concept of Hadith Mawdhu’i (Thematic Hadith) in Contemporary Hadith Scholars Perspective: A Comparative Study of Dirasah Al-Mawdhu‘Iyyah min Al-Hadith and Sharh Al-Mawdhu‘I li Al-Hadith - Ibrahim, Mohd Nor Adzhar; Shamsudin, Roshimah (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
The hadith mawdu’i (thematic hadith) terminology is widely used in contemporary hadith discourse. However, there are confusions in understanding its true concept since several other terms are associated with it namely dirasah al-mawdhu‘iyyah min al-hadith (thematic analysis based on hadith) and sharh al-mawdhu‘i li al-hadith (thematic explanation based on hadith). As such, the purpose of this paper is to study difference opinions amongst the contemporary hadith scholars in comprehending the concept of thematic hadith that gives rise to various definition and concepts. Literature review method based on qualitative research through content analysis design were fully engaged in the data collection as well as data analysis processes. All the definitions and concept of thematic hadith presented by the contemporary hadith scholars in their academic writings were gathered and analyzed to produce a comprehensive depiction. Based on the existing definitions, the findings of this study illustrate that the present-day thematic hadith researchers’ conceptions are split into two camps. The first is the group that deduces thematic hadith as a study upon collection of hadith or upon one particular hadith with a specific theme while the second group infers thematic hadith as thematic lectures. The findings also demonstrate that the difference in understanding thematic hadith between the two groups are from the guidelines and steps in conducting a research. This is the reason why dirasah al-mawdhu‘iyyah min al-hadith is focused on the technical aspect of the initial hadith research such as takhrij (retrieval of hadith) or identifying mukhtalif (contradictions) and so on. While sharh al-mawdhu‘i li al-hadith concentrates on constructive research in depicting a clear picture of the themes that contained in the hadith. Accordingly, the integration between dirasah al-mawdhu‘iyyah min al-hadith and sharh al-mawdhu‘i li al-hadith would produce a holistic research on thematic hadith.